Optimization of a trapezoid-type two-stage Peltier couples for thermoelectric cooling applications. (May 2016) - Lin, Shumin; Yu, Jianlin
Highlights: A trapezoid-type two-stage Peltier couples for thermoelectric cooling is presented. Optimum configuration results in maximum cooling capacity or maximum COP. Comparison of TTPC and STCU reveals the performance advantages of TTPC. Abstract: This paper aims to present a trapezoid-type two-stage Peltier couples (TTPC) for applications in two-stage thermoelectric cooling. By using the TTPC units without intermediate ceramic plates, the TTPC based thermoelectric module may reduce the interstage thermal resistance that could provide better performance. For the TTPC, optimum configuration analyses are performed using developed mathematical model. The simulation result indicates that the Peltier couple leg length allocation ratio between the cold stage and hot stage as well as the shape ratio of trapezoid-type Peltier couple leg at hot stage affect the maximum cooling capacity and coefficient of performance (COP) of TTPC. Moreover, there is an optimum configuration of the TTPC to achieve the optimal maximum cooling capacity and COP at given geometry parameters and operating conditions. The results obtained here may provide some guides for the optimal design and operation of practical the TTPC based thermoelectric module.